Towards a Model for Encoding Correspondence in the TEI: Developing and Implementing <correspDesc> - Stadler, Peter; Illetschko, Marcel; Seifert, Sabine (Journal of the Text Encoding Initiative)
Keywords: Briefe; TEI

Energy demand and efficiency measures in polymer processing: comparison between temperate and Mediterranean operating plants - Khripko, Diana; Schlüter, Alexander; Rommel, Benjamin; Rosano, Michele; Hesselbach, Jens (International Journal of Energy and Environmental Engineering)
Keywords: Primary energy demand; Energy efficiency within industry; Polymer processing

Was heißt guter Geschichtsunterricht? Perspektiven im Vergleich

Rezension zu: Kline, Ronald R.: The Cybernetics Moment. Or Why We Call Our Age the Information Age. Baltimore 2015 - Schmitt, Martin (H-Soz-Kult)

Armut und Gerechtigkeit: Islamische Theologie als gesellschaftspolitische Kraft? - Tatari, Muna (Armut und Gerechtigkeit. Christliche und islamische Perspektiven)

Energy Efficiency in Industrial Areas: Examples, Chances and Challenges. Talk - Schlüter, Alexander

Die historische Perspektive konkret. Begleitband 2 zum Perspektivrahmen Sachunterricht

Die Zeitleiste – Entdeckungen und Erfindungen - Becher, Andrea; Schomaker, Claudia

Answering Fuzzy Conjunctive Queries Over Finitely Valued Fuzzy Ontologies - Borgwardt, Stefan; Mailis, Theofilos; Peñaloza, Rafael; Turhan, Anni-Yasmin (Journal on Data Semantics)
Keywords: Artificial Intelligence; Computer Networks and Communications; Information Systems

Answering Fuzzy Conjunctive Queries Over Finitely Valued Fuzzy Ontologies - Borgwardt, Stefan; Mailis, Theofilos; Peñaloza, Rafael; Turhan, Anni-Yasmin (Journal on Data Semantics)
Keywords: Artificial Intelligence; Computer Networks and Communications; Information Systems

Description Logics Reasoning w.r.t. General TBoxes is decidable for Concrete Domains with the EHD-property - Carapelle, Claudia; Turhan, Anni-Yasmin (Proceedings of the 22nd European Conference on Artificial Intelligence (ECAI 2016))

Geometrische Genauigkeit von Lasersinter-Bauteilen: Einflüsse und Maßnahmen / Dimensional accuracy of polymer laser sintered parts: Influences and measures
In the polymer laser sinter process, part quality depends on many influencing factors along the process chain. For application of the technology in series production and an integration of laser sintered parts into a technical environment, the dimensional accuracy of parts has to be taken into account. Therefore, occurring deviations of the process have to be known to define tolerances for part design. Dimensional deviations and their scattering have to be reduced and homogenized based on process parameters and build job layout. In this work, the dimensional accuracy of laser sintered parts is analyzed for varied parameter values. Influences of different process and geometrical build job parameters on dimensional deviations are figured out. The experimental results allow an evaluation of more and less important influences. Finally, measures are deduced to reduce and homogenize dimensional deviations.

Methode zur Planung eines zukunftsfähigen Produktportfolios - Söllner, Christoph

Entwicklung einer modellbasierten In-the-Loop-Testumgebung für Waschautomaten. - Löffler, Alexander

„Bei dir läuft“ - Neuer Sinn in der Zeit und die migrationsgesellschaftliche Verhandlung des Normverstoßes in der Jugendsprache - Büttner, Denise; Frank, Magnus (Symbolische Ordnung und Bildungsungleichheit in der Migrationsgesellschaft. Interkulturelle Studien)

Die sozial-religiösen Gesprächskreise der „Gülen-Bewegung“. Eine praxeologische Skizze zur Institutionalisierung eines islamischen Bildungsverständnisses - Geier, Thomas; Frank, Magnus; Büttner, Denise (Kulturen der Bildung)

Higher order time discretizations with ALE finite elements for parabolic problems on evolving surfaces - Kovács, Balázs; Power Guerra, Christian Andreas (IMA Journal of Numerical Analysis)
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

Error analysis for full discretizations of quasilinear parabolic problems on evolving surfaces - Kovács, Balázs; Power Guerra, Christian Andreas (Numerical Methods for Partial Differential Equations)
Keywords: Applied Mathematics; Computational Mathematics; Numerical Analysis; Analysis

A-Stable Time Discretizations Preserve Maximal Parabolic Regularity - Kovács, Balázs; Li, Buyang; Lubich, Christian (SIAM Journal on Numerical Analysis)
Keywords: Numerical Analysis; Applied Mathematics; Computational Mathematics

Numerical analysis of parabolic problems with dynamic boundary conditions - Kovács, Balázs; Lubich, Christian (IMA Journal of Numerical Analysis)
Keywords: Applied Mathematics; Computational Mathematics; General Mathematics

A Parallel Numerical Solution Approach for Nonlinear Parabolic Systems Arising in Air Pollution Transport Problems - Karátson, J.; Kovács, Balázs (Mathematical Problems in Meteorological Modelling)

p-adic L-functions for Rankin–Selberg convolutions over number fields - Januszewski, Fabian (Annales mathématiques du Québec; Special Issue in Honor of Glenn Stevens)
Keywords: General Mathematics

On Period Relations for Automorphic L-functions II - Januszewski, Fabian (arXiv:1604.04253)
We study Hecke algebras for pairs $({\mathfrak g},K)$ over arbitrary fields $E$ of characteristic $0$, define the Bernstein functor and give another definition of the Zuckerman functor over $E$. Building on this and the author's previous work on rational structures on automorphic representations, we show that hard duality remains valid over $E$ and apply this result to the study of rationality properties of Sun's cohomologically induced functionals. Our main application are period relations for the special values of standard $L$-functions of automorphic representations of $GL(2n)$ admitting Shalika models.

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (2016 IEEE International Conference on Communications (ICC))

Ziehen und Beweisen mit DGS - Welche Beweiskraft haben für Studierende die Erkenntnisse, die sie im Zugmodus gewinnen? - Werth, Gerda (Beiträge zum Mathematikunterricht)

Regiere dich selbst - Hälterlein, Jens

Mundus pictus. Die bildliche Darstellung astronomischer und geographischer Strukturen in komputistischen Handschriften des 9. Jahrhunderts?! - Englisch, Brigitte (Proceedings of the 6. International Conference on the Science of Computus in Ireland and Europe, Galway 7-11 July, 2016)

Mappa mundi - Die St. Galler Kartentradition des frühen Mittelalters - Englisch, Brigitte

Zusammenhänge zwischen Sprachkompetenz und verstehensorientierter Leistung beim Umgang mit Brüchen - Wessel, Lena; Wilhelm, Nadine (Beiträge zum Mathematikunterricht 2016)

Is grade 7 too late to start with bilingual mathematics courses? An intervention study - Wessel, Lena; Prediger, Susanne; Schüler-Meyer, Alexander; Kuzu, Taha (TSG 32 at 13th International Congress on Mathematical Education, Hamburg, July 2016)

Writer’s overload: A multifaceted concept and its clarification - Karsten, Andrea; Scharlau, Ingrid; Klingsieck, Katrin B. (die hochschullehre)

Schultauglich? Individuelle arbeitsbezogene Verhaltens- und Erlebensmuster von Sportreferendarinnen und -referendaren - Weigelt, Matthias; Lex, Heiko; Kämpfe, Astrid; Klingsieck, Katrin B. (sportunterricht)

Gerhard Ackermann, In Acht und Bann: Lic. Johannes Ackermann (1900-1942), Leipzig 2015 - Janus, Richard (Jahrbuch zur Westfälischen Kirchengeschichte)

Amos - Janus, Richard; Kirsner, Inge

The Wittenberg-Constantinople Negotiations in the 16th and 17th Century. A Form of Early Ecumenical Dialogue? - Janus, Richard (Synthesis)

Das Reziprozitätsprinzip in der Lehre für zukünftige Marktforscher - Corves, Annette; Reis, Oliver (Marktforschung der Zukunft – Mensch oder Maschine? Bewährte Kompetenzen in neuem Kontext)

Modulübergreifend prüfen – Kompetenzorientierung über die Grenzen der Fachdisziplin hinaus - Baumert, Britta; Reis, Oliver (Was ist „Gute Lehre“? Perspektiven für die Hochschuldidaktik)

Kompetenzgraphen zur Darstellung von Prüfungsergebnissen - Lichtenberg, Gerwald; Reis, Oliver (Neues Handbuch Hochschullehre (NHHL) 76)

Reiß, Annike, „Man soll etwas glauben, was man nie gesehen hat“ – Theologische Gespräche mit Jugendlichen zur Wunderthematik. Kassel 2015 - Reis, Oliver (JaBuKi)

Klutz, Philipp: Religionsunterricht vor den Herausforderungen religiöser Pluralität. Münster/New York 2015 - Reis, Oliver (RpB)

Gott und die Menschen: eine komplizierte Beziehung?! In: Leben gestalten 3. Katholischer Religionsunterricht Realschulen und differenzierende Schulformen. Lehrerband - Reis, Oliver

Gott und die Menschen: eine komplizierte Beziehung?! In: Leben gestalten 3. Katholischer Religionsunterricht Realschulen und differenzierende Schulformen - Reis, Oliver

„Öffnen kann ja jeder!“ – von der hohen Kunst des Schließens beim Theologisieren mit Kindern - Reis, Oliver („Da muss ich dann auch alles machen, was er sagt“. Kindertheologie und Unterricht)

Religion lernen. Jahrbuch für konstruktivistische Religionsdidaktik

Was kann eine konstruktivistische Religionsdidaktik von der Narratologie lernen? - Reis, Oliver (Jahrbuch für eine konstruktivistische Religionsdidaktik)

Art. ‚Schulbücher, aktuelle, katholisch, Grundschule / Förderschule‘ - Reis, Oliver (Das Wissenschaftlich-Religionspädagogische Lexikon (WiReLex), Februar 2016)

Art. ‚Schulbücher aktuelle, katholisch, Mittelstufe/Oberstufe‘ - Reis, Oliver (WiReLex, Februar 2016)

Adherence to the WCRF/AICR Dietary Recommendations for Cancer Prevention and Risk of Cancer in Elderly from Europe and the United States: A Meta-Analysis within the CHANCES Project - Jankovic, Nicole; Geelen, Anouk; Winkels, Renate M.; Mwungura, Blaise; Fedirko, Veronika; Jenab, Mazda; Illner, Anne K.; Brenner, Hermann; Ordóñez-Mena, José M.; Kiefte de Jong, Jessica C.; Franco, Oscar H.; Orfanos, Philippos; et al. (Cancer Epidemiology, Biomarkers & Prevention)
Abstract Background: It is unknown whether dietary recommendations for cancer prevention are applicable to the elderly. We analyzed WCRF/AICR recommendations in cohorts of European and U.S. adults ages 60 years and above. Methods: Individual participant data meta-analysis included 362,114 participants (43% women), from seven prospective cohort studies, free from cancer at enrollment. The WCRF/AICR diet score was based on: (i) energy-dense foods and sugary drinks, (ii) plant foods, (iii) red and processed meat, and (iv) alcoholic drinks. Cox proportional hazards regression was used to examine the association between the diet score and cancer risks. Adjusted, cohort-specific HRs were pooled using random-effects meta-analysis. Risk advancement periods (RAP) were calculated to quantify the time period by which the risk of cancer was postponed among those adhering to the recommendations. Results: After a median follow-up of 11 to 15 years across cohorts, 70,877 cancer cases were identified. Each one-point increase in the WCRF/AICR diet score [range, 0 (no) to 4 (complete adherence)] was significantly associated with a lower risk of total cancer [HR, 0.94; 95% confidence interval (CI), 0.92–0.97], cancers of the colorectum (HR, 0.84; 95% CI, 0.80–0.89) and prostate (HR, 0.94; 95% CI, 0.92–0.97), but not breast or lung. Adherence to an additional component of the WCRF/AICR diet score significantly postponed the incidence of cancer at any site by 1.6 years (RAP, −1.6; 95% CI, −4.09 to −2.16). Conclusions: Adherence to WCRF/AICR dietary recommendations is associated with lower risk of cancer among older adults. Impact: Dietary recommendations for cancer prevention are applicable to the elderly. Cancer Epidemiol Biomarkers Prev; 26(1); 136–44. ©2016 AACR.

Alcoholic Beverage Preference and Dietary Habits in Elderly across Europe: Analyses within the Consortium on Health and Ageing: Network of Cohorts in Europe and the United States (CHANCES) Project - Sluik, Diewertje; Jankovic, Nicole; O’Doherty, Mark G.; Geelen, Anouk; Schöttker, Ben; Rolandsson, Olov; Kiefte-de Jong, Jessica C.; Ferrieres, Jean; Bamia, Christina; Fransen, Heidi P.; Boer, Jolanda M. A.; Eriksson, Sture; et al. (PLOS ONE)

Associations among sleep disturbances, nocturnal sleep duration, daytime napping, and incident prediabetes and type 2 diabetes: the Heinz Nixdorf Recall Study - Kowall, Bernd; Lehnich, Anna-Therese; Strucksberg, Karl-Heinz; Führer, Dagmar; Erbel, Raimund; Jankovic, Nicole; Moebus, Susanne; Jöckel, Karl-Heinz; Stang, Andreas (Sleep Medicine)